Deixis and Its Context Used in “Girl in Pieces” Novel by Kathleen Glasglow - Ary Iswanto Wibowo; Nida Nailufar (LPPM Universitas Bina Sarana Informatika, 2018)
Abstract – Deixis is an interesting topic in pragmatic. Deixis is a word that represents something else in utterance. It could be referred to a person, to place, and to time. The reason of choosing deixis is because the languages in the novel often use pragmatic language. The writers used descriptive qualitative method to analyse deixis used in Girl in Pieces novel by Kathleen Glasglow. The procedures are collecting data, processing data, and analysis data. The result of this research indicated that there are three types of deixis used in the novel, person deixis, spatial deixis, and temporal deixis. Person deixis consist of first person deixis to identify the speaker, second person deixis used to appoint the addressee, and third person deixis refer to a person neither the speaker nor the addressee. Spatial deixis used to explain the location of certain utterance. Temporary deixis have function to describe an exact time of utterance. There are 676 deixis found in chapter one of the novel, consist of 569 person deixis, 85 spatial deixis, and 22 temporal deixis. By apprehending the deixis, people could avoid misunderstanding, avoid confusion, and gain more information.